'A certain evolution': a phenomenological study of 24/7 BDSM and negotiating consent. Issue 3 (3rd July 2022) - Cascalheira, Cory J.; Thomson, Amy; Wignall, Liam
ABSTRACT: BDSM as a full-time lifestyle is stigmatised and underexamined as a phenomenon. Previous studies have investigated 24/7 sadomasochism (SM), 24/7 dominance and submission (D/s), or total power exchange (TPE), yet 24/7 BDSM remains under researched. Using a social constructionist and sexual diversity framework, we used insider knowledge to recruit four participants: a female slave/masochist, a male sadist, a female submissive, and a male dominant/protector. Interpretative phenomenological analysis revealed four superordinate and 10 subordinate themes: routes towards the fundamentals (sexually explicit resources, kink-related experiences), full-on lifestyle (self-in-role, flexible rules, shades of play, polyamory), dynamic consent (honesty, contextual communication), and practicalities (challenges, benefits). Our findings suggested that 24/7 BDSM is a socially constructed, consensual, full-time adherence to kink-related roles and behaviours untethered to time-limited scenes, woven into other life domains, and operating as an umbrella term to encompass other perpetual power dynamics. The themes contribute to the debate of kink as a sexual identity or serious leisure. We concluded that the centrality of self-in-role coupled with leisure features support 24/7 BDSM as an erotic lifestyle. Implications for sexual diversity, sex education, clinical guidelines, and social justice are discussed.